Case report: Association between PTEN-gene variant and an aggressive case of multiple dAVFs - Jong-A-Liem, Glaucia Suzanna; Sarti, Talita Helena Martins; dos Santos, Mariusi Glasenapp; Giacon, Luciano Marcus Tirotti; Wuo-Silva, Raphael; Baeta, Alex Machado; de Campos Filho, José Maria; Chaddad-Neto, Feres (Frontiers in Neurology, 2024)
Introduction: Mutations of the PTEN gene have been associated with a spectrum of disorders called PTEN Hamartoma syndrome and predispose the development of various types of tumors and vascular anomalies. Its phenotypic spectrum includes Cowden syndrome (CS), Bannayan-Riley-Ruvalcaba syndrome (BRRS), Proteus syndrome, autism spectrum disorders (ASD), some sporadic cancers, Lhermitte -Duclos disease (LDD) and varied types of associated vascular anomalies.A previously healthy 27-year-old woman has been experiencing visual scintillating scotomas and mild chronic headaches for the past two years. Initial CT and MRI scans did not reveal any abnormalities, but the possibility of pseudotumor cerebri was considered. Further cerebral angiography showed a posterior fossa dural arteriovenous fistula (dAVF), which was initially treated through embolization. However, in spite of proper treatment, this patient experienced multiple recurrent dAVFs in different locations, requiring multiple embolization and surgeries. Despite exhibiting altered cerebral perfusion and hemodynamics, the patient did not display any significant symptoms until she experienced a sudden stroke resulting from deep venous thrombosis. This thrombosis was not associated with any medical procedures or medication use. A comprehensive analysis was conducted due to the aggressive nature of the dAVFs. Surprisingly, exome sequencing of a blood sample revealed a PTEN gene variant in chromosome 10, indicative of Cowden Syndrome. However, no tumors or other vascular lesions were detected in other systems which would constitute Cowden Syndrome. The rapid formation of multiple and complex dAVF, coupled with the absence of criteria for any other PTEN-related syndrome, unequivocally leads to the presentation of a novel phenotype of PTEN germline variant.